ANALISIS PEMAHAMAN KONSEP IPS PADA SISWA KELAS IV DI SD NEGERI 01 TANJUNG TEBAT - Lola Mida Andikasari; Tanzimah Tanzimah; Ida Suryani (Universitas Negeri Medan, 2022)
Abstract: Analysis of Social Science Concept Understanding of Fourth Grade Students at SD Negeri 01 Tanjung Tebat. This study aims to analyze and describe the understanding of social studies concepts in fourth grade students at SD Negeri 01 Tanjung Tebat using a qualitative descriptive method. The object of this research is understanding the concept of social studies and informants in this study are teachers and fourth grade students of SD Negeri 01 Tanjung Tebat. Data collection techniques in the form of tests, interviews and documentation. Data analysis used the Milles and Huberman design, namely data reduction (data reduction), data presentation (data display), and drawing conclusions (verification). Results Based on the research, it shows that the understanding of social studies concepts in fourth grade students at SD Negeri 01 Tanjung Tebat is in the sufficient category, obtained from the average test score of 68.05. To present the indicators of understanding the concept of Exemplifying 56%, Classifying 73%, Comparing 59%, is 68% and Summing up 77%. Keywords: Analysis, Understanding Social Science Concepts Abstract : Analisis Pemahaman Konsep Ips Pada Siswa Kelas IV Di SD Negeri 01 Tanjung Tebat. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan pemahaman konsep IPS pada siswa kelas IV di SD Negeri 01 Tanjung Tebat dengan menggunakan metode deskriptif kualitatif . Objek pada penelitian ini yaitu pemahaman konsep IPS dan Informan pada penelitian ini yaitu Guru dan siswa kelas IV SD Negeri 01 Tanjung Tebat. Teknik pengumpulan data berupa tes, wawancara dan dokumentasi. Data dianalisis menggunakan rancangan Milles dan Huberman yaitu reduksi data (data reduction), penyajian data (data display), dan penarikan kesimpulan (verification). Berdasarkan hasil penelitian menunjukkan bahwa pemahaman konsep IPS pada siswa kelas IV di SD Negeri 01 Tanjung Tebat dalam kategori cukup diperoleh dari rata-rata nilai tes yaitu 68,05. Untuk presentase pada indikator pemahaman konsep Mencontohkan 56%, Mengklasifikasikan 73%, Membandingkan 59%, Menjelaskan 68% dan Menyimpulkan 77%. Kata Kunci : Analisis, Pemahaman Konsep IPS